Protein and polysaccharide conjugates as emerging scaffolds for drug delivery systems. (2017) - Xu, Amy Y.; Melton, Laurence D.; Williams, Martin A.K.; McGillivray, Duncan J.
Protein and polysaccharide conjugates are ideal for developing coatings for medical scaffolds and drug delivery systems owing to their high biocompatibility and biodegradability. In this study, we are conjugating a hydrophobic protein zein with a hydrophilic polysaccharide, pectin. A specific covalent linkage is introduced between the reducing end of pectin and the amine groups of zein that are surface accessible. After successful coupling of pectin to zein, the conjugate is water-soluble. A film was prepared with the zein-pectin conjugates on a hydrophilic silica surface. SEM shows that the film is mainly composed of zein nanoparticles coated with pectin, and these nanoparticles arrange themselves into individual arrays that are separated by several wide channels. Films with such nanostructures can be exploited for developing bioactive coatings.